Extended spectrum β-lactamase and antibiotic suspectibility of escherichia coli grown in urinary isolates [İdrar örneklerinde üretilen Escherichia coli suşlarında genişlemiş spektrumlu beta-laktamaz varlığı ve antibiyotik duyarlılıkları] - (:unkn) unknown (Logos Medical Publishing, 2014)
In recent years, Extended Spectrum ß-Lactamase (ESBL) rates in Escherichia coli which is the causative agent of urinary tract infections, are increasing. In our study, we found ESBL positivity with female and male patients as 9,4 % and 24,3 % respectively. ESBL rate was detected as 9,7% for patients under the age of 65 and 17,8 % for those 65 years and older. These ESBL rates were statistically significant higher in patients over 65 years of age and male sex. The highest antibiotic susceptibility rates of ESBL-positive strains belonged to carbapenems (meropenem 99.7 %, imipenem 99.3% and ertapenem 97.3 %). In patients who were admitted to the clinic with complaints of urinary tract infections, the choice of antibiotics taking ESBL risk factors into consideration will increase the success of treatment. © 2014, Logos Medical Publishing. All rights reserved.
Keywords: Antibiotic susceptibility; Escherichia coli; Extended Spectrum β-Lactamase (ESBL)